4-Chloro-2-methylphenoxyacetic acid photo-reduction with sulfite excitation under UV irradiation: Kinetics, energy consumption, operational variables and toxicology with Daphnia magna - Farzaneh Totoni Mofrad; Ahmad Jonidi Jafari; Majid Kermani; Mahdi Farzadkia; Ali Esrafili (Desalination and Water Treatment)
4-chloro-2-methylphenoxyacetic acid (MCPA) is persistent and emerging organic substances that cannot be removed by bio-degradation and simply enter the environment. Therefore, for its photo-reduction, new methods are needed, including advanced photo- reduction process. This work deals with use of MCPA photo-reduction process based on sulfite excitation under UV irradiation. The optimal pH was 9 and molar ratio 1:1 MCPA: Sulfite, and complete photo-reduction of MCPA was reached after 15 min reaction time. The effect of various parameters were optimized using one factor at time (OFAT). In kinetic investigation, reaction constant (kobs) reduced from 0.2794 to 0.1645 min−1 when MCPA concentration increase from 5 to 25 mg L−1. In addition, the reaction rate (robs) increased 1.397 to 4.1125 mg L−1 min−1. Also, EEO was determined by kinetics and IUPAC methods, which showed that the quantity of energy consumption increases with increasing MCPA concentration. 2-(o-tolyloxy)acetic acid, 1-ethoxy-2,4-dimethylbenzene, toluene, (E)− 2-(prop-l-en-l-yloxy)acetic acid, (E)− 1-ethoxyprop-1-ene, and (E)− 1-ethoxyprop-1-ene identified as intermediates. Improvement of biodegradability was investigated with tow indicators include AOS and COS and shows that with the passage of time, the improvement of degradability is noticeable. For explored the mineralization rate, COD, TOC removal efficiency reach > 99%, 74.7%, and 62%, respectively after 120 min reaction time. The acute toxicity test by Daphnia magna was utilized to assess the toxicity of UV/Sulfite process effluent, results showed that EC50 (96-hour) and toxicity unit (TU) were equal to 10.53 mg L−1 and 9.94 TU in raw solution of MCPA and 93.50 mg L−1 and 1.07 TU in treated solution respectively, which the effluent from the process was reduced significantly than the raw solution of pollutant. It can be disclosed that the UV/Sulfite process has a good performance in pollutant conversion to simple intermediate and improving biodegradability as well as wastewater detoxification to reach environmental standards.